Subjective Well-being in Long-Distance Marriage: The Role of Family Functioning, Financial Decision-Making, and Loneliness - Taufiiqoh, Maitsaa Rifdah; Krisnatuti, Diah; Muflikhati, Istiqlaliyah (Journal of Educational, Health and Community Psychology, 2025)
Long-distance marriage refers to a condition in which spouses live apart, potentially affecting their subjective well-being. This study aims to analyze the influence of family functioning, financial decision-making, and loneliness on subjective well-being in families experiencing long-distance marriage. A mixed-method approach was employed with 50 male and 55 female respondents. The findings indicate that family functioning scores were higher among female respondents compared to males, while no significant differences were found in other variables. The results of the SEM analysis show that family functioning on women had a significant positive effect, while loneliness on men had a significant negative effect on subjective well-being. Financial decision-making showed no significant impact. Families are encouraged to maintain shared spiritual routines and emotional connection, and engage in affective communication and social interaction to alleviate loneliness. Future research is expected to incorporate children‘s perspectives to better understand family functioning in long-distance marriage families.